Corrigendum to “Trifluoroacetic acid and ocular malformations in rabbits: Proposed mechanisms of action” [Reprod. Toxicol. 143 (2026) 109258] - Julian French; Jason Manton; Maaike E. Schutte; Stephanie Melching-Kollmuss; Steffen Schneider; Ivana Fegert; Anja Hueser; Birgit Neumann; Michael Temerowski; Lisa Bertomeu; Richard Bartlett (Reproductive Toxicology, 2026)

Trifluoroacetic acid and ocular malformations in rabbits: Proposed mechanisms of action - Julian French; Jason Manton; Maaike E. Schutte; Stephanie Melching-Kollmuss; Steffen Schneider; Ivana Fegert; Anja Hueser; Birgit Neumann; Michael Temerowski; Lisa Bertomeu; Richard Bartlett (Reproductive Toxicology, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Mycorrhizal identity and light shape tree seedling biomass responses in plant–soil feedbacks - Sarah McCarthy-Neumann; Katherine E. A. Wood; Richard K. Kobe (Plant and Soil, 2026)
Aims Plant–soil feedbacks (PSFs) are key drivers of forest composition and diversity, yet their direction and magnitude may depend on the mycorrhizal identity of interacting species, environmental conditions, and experimental context. Methods We conducted complementary greenhouse and field experiments using Acer rubrum L., Acer saccharum Marsh., Prunus serotina Ehrh. (all arbuscular mycorrhizal [AM] species), and Quercus alba L., and Quercus rubra L. (all ectomycorrhizal [EM] species) to test how biomass-based PSFs vary with mycorrhizal matching between seedlings and adult trees, light availability, and soil microbial communities. Seedlings were grown in soil conditioned by conspecifics, conmycorrhizal heterospecifics, or heteromycorrhizal heterospecifics under controlled and natural light regimes. Results Consistent with expectations, AM species consistently exhibited negative PSFs under low light, and EM species tended to show more positive PSFs, but this pattern was contingent on light and greenhouse versus field setting. For AM species, negative PSFs occurred primarily under low light and were neutralized or reversed under higher light. EM species showed generally more positive PSFs across light levels and settings, although species-specific differences emerged. PSFs were driven largely by conspecific soil conditioning, with limited influence from the mycorrhizal identity of heterospecific neighbors. Results from greenhouse versus field settings diverged, with field PSFs sometimes attenuated or reversed, particularly for Q. alba. Conclusions These findings highlight that biomass-based PSFs are not fixed species traits but context-dependent outcomes influenced by mycorrhizal type, light availability, and environmental setting. Incorporating these factors is essential for predicting how PSFs influence seedling recruitment, forest dynamics, and biodiversity.

A quantitative modeling framework to understand the physiology of the hypothalamic-pituitary-adrenal axis and interaction with cortisol replacement therapy - Davide Bindellini; Robin Michelet; Linda B. S. Aulin; Johanna Melin; Uta Neumann; Oliver Blankenstein; Wilhelm Huisinga; Martin J. Whitaker; Richard Ross; Charlotte Kloft (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Congenital adrenal hyperplasia (CAH) is characterized by impaired adrenal cortisol production. Hydrocortisone (synthetic cortisol) is the drug-of-choice for cortisol replacement therapy, aiming to mimic physiological cortisol circadian rhythm. The hypothalamic-pituitary-adrenal (HPA) axis controls cortisol production through the pituitary adrenocorticotropic hormone (ACTH) and feedback mechanisms. The aim of this study was to quantify key mechanisms involved in the HPA axis activity regulation and their interaction with hydrocortisone therapy. Data from 30 healthy volunteers was leveraged: Endogenous ACTH and cortisol concentrations without any intervention as well as cortisol concentrations measured after dexamethasone suppression and single dose administration of (i) 0.5–10 mg hydrocortisone as granules, (ii) 20 mg hydrocortisone as granules and intravenous bolus. A stepwise model development workflow was used: A newly developed model for endogenous ACTH and cortisol was merged with a refined hydrocortisone pharmacokinetic model. The joint model was used to simulate ACTH and cortisol trajectories in CAH patients with varying degrees of enzyme deficiency, with or without hydrocortisone administration, and healthy individuals. Time-dependent ACTH-driven endogenous cortisol production and cortisol-mediated feedback inhibition of ACTH secretion processes were quantified and implemented in the model. Comparison of simulated ACTH and cortisol trajectories between CAH patients and healthy individuals showed the importance of administering hydrocortisone before morning ACTH secretion peak time to suppress ACTH overproduction observed in untreated CAH patients. The developed framework allowed to gain insights on the physiological mechanisms of the HPA axis regulation, its perturbations in CAH and interaction with hydrocortisone administration, paving the way towards cortisol replacement therapy optimization. Graphical Abstract

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

Multistage formation of the titanite-centered ocellar texture in magma mixing zones: New insights from field, petrographic and mineralogic evidence in the Paleoproterozoic Mineiro belt, Brazil - Charlys Vaz de Sant’Anna Neves; Ciro Alexandre Ávila; Reiner Neumann; Everton Bongiolo; Fabiano Richard Leite Faulstich; Wilson Teixeira (Journal of South American Earth Sciences, 2023)

Preserved interactions between acid and intermediate magmas in a 2.15–2.10 Ga Rhyacian continental arc: Insights from petrographic, geochemical and isotopic data of the Macuco de Minas metagranitoid, Mineiro belt, Brazil - Charlys Vaz de Sant'Anna Neves; Ciro Alexandre Ávila; Everton Marques Bongiolo; Reiner Neumann; Wilson Teixeira; Fabiano Richard Leite Faulstich; Mônica Heilbron; Mauro César Geraldes; Cláudio de Morisson Valeriano (Lithos, 2023)

Monazite age and composition from a granite-pegmatite system: A link between pegmatites of the São João del Rei Pegmatitic Province and the newly defined high-K Restinga Metagranite, Minas Gerais, Brazil - Sarah Siqueira da Cruz Guimarães Sousa; Ciro Alexandre Ávila; Reiner Neumann; Fabiano Richard Leite Faulstich; Ricardo Scholz (Journal of South American Earth Sciences, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Complex and flexible catabolism in Aromatoleum aromaticum pCyN1 - Patrick Becker; Annemieke Döhmann; Lars Wöhlbrand; Daniela Thies; Christina Hinrichs; Ramona Buschen; Daniel Wünsch; Meina Neumann‐Schaal; Dietmar Schomburg; Michael Winklhofer; Richard Reinhardt; Ralf Rabus (Environmental Microbiology, 2022)
Summary Large quantities of organic matter are continuously deposited, and (a)biotic gradients intersect in the soil–rhizosphere, where biodegradation contributes to the global cycles of elements. The betaproteobacterial genus Aromatoleum comprises cosmopolitan, facultative denitrifying degradation specialists. Aromatoleum aromaticum . pCyN1 stands out for anaerobically decomposing plant‐derived monoterpenes in addition to monoaromatic hydrocarbons, polar aromatics and aliphatics. The catabolic network's structure and flexibility in A . aromaticum pCyN1 were studied across 34 growth conditions by superimposing proteome profiles onto the manually annotated 4.37 Mbp genome. Strain pCyN1 employs three fundamentally different enzymes for C–H‐bond cleavage at the methyl groups of p ‐cymene/4‐ethyltoluene, toluene and p ‐cresol respectively. Regulation of degradation modules displayed substrate specificities ranging from narrow (toluene and cyclohexane carboxylate) via medium‐wide (one module shared by p ‐cymene, 4‐ethyltoluene, α‐phellandrene, α‐terpinene, γ‐terpinene and limonene) to broad (central benzoyl‐CoA pathway serving 16 aromatic substrates). Remarkably, three variants of ATP‐dependent (class I) benzoyl‐CoA reductase and four different β‐oxidation routes establish a degradation hub that accommodates the substrate diversity. The respiratory system displayed several conspicuous profiles, e.g. the presence of nitrous oxide reductase under oxic and of low‐affinity oxidase under anoxic conditions. Overall, nutritional versatility in conjunction with network regulation endow A . aromaticum pCyN1 with broad adaptability.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Making the invisible visible: tracing the origins of plants in West African cuisine through archaeobotanical and organic residue analysis - Julie Dunne; Alexa Höhn; Katharina Neumann; Gabriele Franke; Peter Breunig; Louis Champion; Toby Gillard; Caitlin Walton-Doyle; Richard P. Evershed (Archaeological and Anthropological Sciences, 2022)

Polyphase enrichment and redistribution processes in silver-rich mineral associations of the hydrothermal fluorite-barite-(Ag-Cu) Clara deposit, SW Germany - Maximilian F. Keim; Benjamin F. Walter; Udo Neumann; Stefan Kreissl; Richard Bayerl; Gregor Markl (Mineralium Deposita, 2019)

A prickly problem: developing a volunteer-friendly tool for monitoring populations of a terrestrial urban mammal, the West European hedgehog (Erinaceus europaeus) - Ben Williams; Nittanjyot Mann; Jessica L. Neumann; Richard W. Yarnell; Philip J. Baker (Urban Ecosystems, 2018)

Strong sustainability in coastal areas: a conceptual interpretation of SDG 14 - Barbara Neumann; Konrad Ott; Richard Kenchington (Sustainability Science, 2017)

Effects, but no interactions, of ubiquitous pesticide and parasite stressors on honey bee ( A pis mellifera ) lifespan and behaviour in a colony environment - Gina Retschnig; Geoffrey R. Williams; Richard Odemer; Janina Boltin; Cornelia Di Poto; Marion M. Mehmann; Peter Retschnig; Pius Winiger; Peter Rosenkranz; Peter Neumann (Environmental Microbiology, 2015)
Summary Interactions between pesticides and parasites are believed to be responsible for increased mortality of honey bee ( A pis mellifera ) colonies in the northern hemisphere. Previous efforts have employed experimental approaches using small groups under laboratory conditions to investigate influence of these stressors on honey bee physiology and behaviour, although both the colony level and field conditions play a key role for eusocial honey bees. Here, we challenged honey bee workers under in vivo colony conditions with sublethal doses of the neonicotinoid thiacloprid, the miticide tau‐fluvalinate and the endoparasite N osema ceranae , to investigate potential effects on longevity and behaviour using observation hives. In contrast to previous laboratory studies, our results do not suggest interactions among stressors, but rather lone effects of pesticides and the parasite on mortality and behaviour, respectively. These effects appear to be weak due to different outcomes at the two study sites, thereby suggesting that the role of thiacloprid, tau‐fluvalinate and N . ceranae and interactions among them may have been overemphasized. In the future, investigations into the effects of honey bee stressors should prioritize the use of colonies maintained under a variety of environmental conditions in order to obtain more biologically relevant data.

Climate change risks to US infrastructure: impacts on roads, bridges, coastal development, and urban drainage - James E. Neumann; Jason Price; Paul Chinowsky; Leonard Wright; Lindsay Ludwig; Richard Streeter; Russell Jones; Joel B. Smith; William Perkins; Lesley Jantarasami; Jeremy Martinich (Climatic Change, 2015)

Tomographic myocardial perfusion imaging using a hybrid time-modulated coded-aperture collimator system - Donald Richard Neumann; Yau Hwang Lee; Gerald M. Burma (Annals of Biomedical Engineering, 1988)